O comprometimento do cooperado com a cooperativa - Oliveira, José Rudnei de (2007)
Evaluating the associated commitment to their cooperative society, seeking organization invigoration in the market is the theme of this Case Study (Multicase), having a descriptive and quantitative approach. It was looked for answers to suggest administrative actions to be used by the cooperative system in São Gabriel city -RS, seeking to increase the participation and the link between its members and the cooperative. The objectives of the present work seek, besides evaluating the associated commitment, investigate if: the member negociates with other companies; which reasons him to participate in the cooperative; what stimulates or discourages him to participate in the cooperative company and to investigate how the system credibility is under the member point-of-view. In the search for data questionnaires were applied to the members of three cooperatives in São Gabriel city -RS, being the content of the collected data analyzed through statistical programs for evaluation and conclusions presented later, generating alternative suggestions to make possible the cooperative system invigoration. Concluding the work, it was noticed that the accociated commitment is inferior to the necessary to mantain the cooperative competitive